2013
DOI: 10.1016/j.ijrobp.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Second Solid Cancers After Radiation Therapy: A Systematic Review of the Epidemiologic Studies of the Radiation Dose-Response Relationship

Abstract: Rapid innovation in radiotherapy techniques has resulted in an urgent need for risk projection models for second cancer risks from high-dose radiation exposure, since direct observation of the late-effects of newer treatments will require patient follow-up for a decade or more. However, the patterns of cancer risk after fractionated high-dose radiation are much less well understood than those after lower-dose exposures (0.1–5 gray (Gy)). In particular, there is uncertainty about the shape of the dose-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 46 publications
5
156
4
3
Order By: Relevance
“…This analysis also showed that HT is Figure 5 also indicates that overall, the ERR and LQ calculation models may be a more accurate and consistent means of calculation because they contain a narrower spread across the patient data as indicated by their thinner boxes and shorter distances between maximum and minimum data values, in general. This finding is in agreement with recent reports, which state that general risk models tend to overestimate secondary cancers compared to epidemiological studies of patients treated with radiation therapy (48).…”
Section: Age Analysissupporting
confidence: 93%
“…This analysis also showed that HT is Figure 5 also indicates that overall, the ERR and LQ calculation models may be a more accurate and consistent means of calculation because they contain a narrower spread across the patient data as indicated by their thinner boxes and shorter distances between maximum and minimum data values, in general. This finding is in agreement with recent reports, which state that general risk models tend to overestimate secondary cancers compared to epidemiological studies of patients treated with radiation therapy (48).…”
Section: Age Analysissupporting
confidence: 93%
“…They also confirmed that the risk varied according to the tissue of origin of the second cancer. 81 Since the evidence mostly confirms an approximately linear risk of RIC, the data obtained from patients with cancer treated with high doses can be used to give some guidance as to the lesser risks of RIC after exposure to intermediate doses. However, treatment protocols/fractionation regimens will often be different, so any extrapolation from highdose studies must be interpreted with caution.…”
Section: Studies Providing Indirect Evidence Of the Excess Risk Of Ramentioning
confidence: 99%
“…However, the quantitative relationship between low-medium dose levels and the induction of secondary cancer is not clinically proven. Risk models exist, [22][23][24] but the clinical validation is vague. Again, the ALARA principle should be applied.…”
mentioning
confidence: 99%